External Influence of Early Childhood Establishment of Gut Microbiota and Subsequent Health Implications - Munyaka, Peris Mumbi; Khafipour, Ehsan; Ghia, Jean-Eric (Frontiers in Pediatrics, 2014)
Postnatal maturation of immune regulation is largely driven by exposure to microbes. The gastrointestinal tract is the largest source of microbial exposure, as the human gut microbiome contains up to 1014 bacteria, which is ten times the number of cells in the human body. Several studies in recent years have shown differences in the composition of the gut microbiota in children who are exposed to different conditions before, during and early after birth. A number of maternal factors are responsible for the establishment and colonization of gut microbiota in infants, such as the conditions surrounding the prenatal period, time and mode of delivery, diet, mother’s age, BMI, and smoking status, household milieu, socioeconomic status, breastfeeding and antibiotic use, as well as other environmental factors that have profound effects on the microbiota and on immunoregulation during early life. Early exposures impacting the intestinal microbiota are associated with the development of childhood diseases that may persist to adulthood such as asthma, allergic disorders (atopic dermatitis, rhinitis), chronic immune-mediated inflammatory diseases, type 1 diabetes, obesity, and eczema. This overview highlights some of the exposures during the pre and postnatal time periods that are key in the colonization and development of the gastrointestinal microbiota of infants, as well as some of the diseases or disorders that occur due to the pattern of initial gut colonization.